THREE-DIMENSIONAL VELOCITY STRUCTURE OF THE CRUST IN CENTRAL LAKE BAIKAL FROM LOCAL SEISMIC TOMOGRAPHY - L. Yu. Eponeshnikova; A. A. Duchkov; D. P.-D. Sanzhieva; S. V. Yaskevich (Геодинамика и тектонофизика, 2023)
This work deals with the importance of studying seismicity and deep structure of the Earth’s crust in the region of the Baikal rift zone. The study presents a three-dimensional velocity structure of the Earth’s crust in the central part of Lake Baikal, obtained from the results of tomographic inversion of the travel times of P- and S-waves from more than 800 seismic events. Synthetic tests provide substantiation for the resolution of the tomographic inversion algorithm. The seismic structure of the crust was obtained to a depth of 35 km and has a direct relationship with the geological structure. The three-dimensional distributions of seismic P- and S-wave velocity anomalies are in good agreement with each other.The sharp contrast between the anomalies may indicate a difference in the material composition of the basement of the Central Baikal basin. At a 15-km depth below the Selenga River delta, there is observed a strong low-velocity anomaly which confirms the presence of a thick sedimentary cover therein. In the basement (at depths of 20 km or greater), to the northeast of the intersection between the Delta fault and the Fofanov fault, there occurs a high-velocity anomaly elongated towards the Olkhon Island. This anomaly is probably related to a rigid block in the earth’s crust. The same depths, on the western side of the Baikal-Buguldeika fault, show a reduced Vp/Vs ratio: 1.56–1.65 versus 1.70–1.75 in the adjacent areas. This indicates another type of basement rock composition and the presence of consolidated matter there.Besides, there has been made a more accurate hypocenter determination for further comparison between seismic events and active fault structures. For the central part of Lake Baikal, the distribution of seismicity mainly corresponds to depths of 10–22 km. The situation is different below the Selenga Delta – the only area where seismicity is observed at depths greater than 22 km, – which can be attributed to complex fault interactions.The velocity anomalies discussed herein are confined to reliably identified active faults and correlate well with the distribution of seismicity and gas hydrate structures.